Glycoside hydrolase–mediated glucomannan catabolism in Segatella copri , a target of microbiota-directed foods for malnourished children - Cyrus Zhou; Matthew C. Hibberd; Evan M. Lee; Bo Pilgaard; Marlene Vuillemin; Emma Kiehn; Suzanne Henrissat; Marie A. Crane; Jiye Cheng; Lara Pfaff; Anne S. Meyer; Jesper Holck; et al. (Proceedings of the National Academy of Sciences, 2025)
Evidence is emerging that perturbed postnatal gut microbiota development is causally related to childhood undernutrition. Clinical trials in undernourished Bangladeshi children found that a polysaccharide-rich, microbiota-directed complementary food (MDCF-2) designed to repair this perturbation produced superior ponderal and linear growth compared to a standard ready-to-use supplementary food. Subsequent analyses disclosed several candidate bioactive polysaccharides in the MDCF and their bacterial targets, notably strains of Segatella copri that possess carbohydrate-active enzymes (CAZymes) organized into polysaccharide utilization loci (PULs) targeting these glycans. A Bangladeshi S. copri isolate (BgF5_2) containing these PULs metabolized MDCF-2 glycans and promoted MDCF-dependent weight gain in a gnotobiotic mouse model emulating the clinical trials. Identifying prebiotic mixtures that mimic the effects of MDCF-2 would offer new options for treatment and prevention. Here, we describe a CAZyme-based approach to characterize the effects of glucomannan, a component of MDCF obtainable from sustainable sources, on growth and gene expression in S. copri BgF5_2 in vitro and in gnotobiotic mice. Biochemical characterization of purified CAZymes expressed by two of its MDCF-2 and glucomannan-targeted PULs disclosed a multifunctional GH26|GH5_4 CAZyme, inducible by glucomannan, that degrades several bioactive MDCF-2 glycans; glucomannan, arabinoxylan, xyloglucan, and mixed-linkage β-glucan. Our data suggest that this CAZyme functions as a multisubstrate “sentinel” that can produce diverse oligosaccharides from a variety of β-linked glycans, with each oligosaccharide able to induce corresponding PULs and non-PUL enzymes. This observation, plus the restricted distribution of the multifunctional CAZyme among S. copri strains, may partially explain strain responsiveness to MDCF-2.